Molecular characterization of colistin-resistant Klebsiella pneumoniae isolates and their conjugative mcr-carrying plasmids - Cheng-Yen Kao; Pei-Yun Kuo; Chih-Chieh Lin; Ya-Yu Cheng; Ming-Cheng Wang; Yu-Chen Chen; Wei-Hung Lin (Elsevier, 2024)
Background: This study aimed to characterize colistin-resistant K. pneumoniae (CoRKp) strains isolated from patients with urinary tract infections and bacteremia between 1999 and 2022 at a tertiary teaching hospital in Taiwan. Methods: A total of 1966 K. pneumoniae isolates were collected, among which 21 strains were identified as CoRKp. The antimicrobial susceptibility of these CoRKp strains to 19 antibiotics was assessed. The genome characteristics of 21 CoRKp strains were determined by Nanopore-Illumina hybrid whole genome sequencing. Additionally, conjugation assays were conducted to determine the transferability of plasmids carrying mcr genes to K. pneumoniae ATCC BAA-1706 and E. coli C600. The larvae infection model was used to analyze the differences in virulence between transconjugants and recipient strains. Results: Among the 21 CoRKp, 12 were multidrug-resistant, and four were extensively drug-resistant. The distribution of sequence types (STs) and K types among the CoRKp strains was quite diverse, and ST307 (5 strains) and K64 (3 strains) dominated in CoRKp. The insertion elements IS903B and ISVsa5, were found to inactivate mgrB of 1 and 2 CoRKp isolates, respectively. Moreover, 1, 4, 6, and 1 missense mutations of PhoQ, PmrA, PmrB, and MgrB, were identified in 21 CoRKp. Only two isolates SC-KP169 and SC-KP585 carried mcr-1 and mcr-8, respectively. The plasmid pSC-KP169-1 could be transferred inter- and intra-genus and contributed to the virulence of K. pneumoniae to larvae. In contrast, the plasmid pSC-KP585-1 could be transferred to E. coli but could not affect its virulence to larvae. Conclusions: We identified 21 CoRKp from 1966 isolates and found a conjugative plasmid carrying mcr-1 gene that contributed to the virulence of K. pneumoniae to larvae.